EXAMINING THE RELATIONSHIP BETWEEN PRESCHOOL TEACHERS’ STRESS LEVELS AND SCHOOL CLIMATE - Sezer, Türker; Karaca Gelgör, Fatıma (International Scientific Journal Vision, 2025)
This study, structured as a literature review, explores the concepts of ’Teacher Stress’ and ’School Climate.’ Researchers have shown increasing interest in teacher stress; however, studies focusing on preschool teachers’ stress remain limited (Hu et al., 2019). Research on stress among preschool educators consistently highlights its profound negative impact on both teachers’ well-being and classroom dynamics. High stress levels are closely linked to burnout and emotional exhaustion, which in turn diminish teachers’ self-efficacy and motivation, particularly in managing challenging classroom behaviors (Roberts et al., 2020). Furthermore, elevated stress disrupts the classroom climate, weakens teacher-student relationships, and hinders children’s socio-emotional development (Sönmez & Kolaşınlı, 2020; Jeon et al., 2018). This stress also reduces teachers’ confidence in managing classroom dynamics, adversely affecting their ability to create a supportive learning environment (Zhai et al., 2011). Collectively, these findings underscore the need for interventions that support preschool teachers in managing occupational stress, thereby enhancing both educators’ resilience and classroom quality. The aim of this study is to contribute to the literature by examining the factors influencing preschool teachers’ stress levels and their relationship with school climate, which is considered one of the primary causes of stress.